Rhinosporidiosis and the pond - M Prakash; J Carlton Johnny (Wolters Kluwer Medknow Publications, 2015)
Rhinosporidiosis is a fungal disease caused by the organism Rhinosporidum seeberi. The life cycle and mode of infection are vague, and there are many hypothesis on it. Its prevalence in the world is unique as it is only limited to certain regions like India, Pakistan and Sri Lanka. We have tried to correlate the various factors, which will probably be associated with this pattern of prevalence of the disease. We have included factors like community practices, climatic conditions, rain fall pattern, water physiochemical properties, zoonotic and the aquatic organism composition in the specified regions. Thus, it serves as a wholesome idea of why the disease must only be prevalent in certain parts of the world.